Application of Black Titanium Dioxide and Its Composite Materials in Photocatalytic Degradation of Water Pollutants - Morosky, Alejandra; Winter, Steven; Mabry, Moley (Journal of Functional Materials and Applied Engineering, 2022)
Photocatalysis has demonstrated tremendous potential across numerous application fields owing to its high efficiency, environmental friendliness, and low cost. Conventional titanium dioxide (TiO₂), a widely utilized photocatalytic material, possesses a large bandgap, restricting its light absorption solely to the ultraviolet region. Furthermore, the rapid recombination of photogenerated electron-hole pairs in TiO₂ limits its photocatalytic efficiency. Introducing defects such as oxygen vacancies onto the TiO₂ surface yields black titanium dioxide (TiO₂₋ₓ), which enhances its response performance and quantum efficiency in the visible and near-infrared regions by narrowing the bandgap and increasing active sites, thereby improving photocatalytic activity. Consequently, the synthesis and modification of black titanium dioxide have emerged as prominent research hotspots. This review systematically examines the critical defect structures of TiO₂₋ₓ and their characterization methodologies, summarizes its synthesis routes, and discusses modification strategies. Furthermore, it provides a focused analysis of the applications of TiO₂₋ₓ and its composite materials in the photocatalytic degradation of aquatic pollutants, accompanied by an in-depth summary of degradation mechanisms. Finally, the challenges and opportunities confronting TiO₂₋ₓ and its composites in the future remediation of environmental water pollution are outlined.